The Mellops go diving for treasure - Ungerer, Tomi, 1931- (Phaidon Press, 2011)
"One day Mr. Mellops finds a dusty old trunk in his attic, and before they know it, the family are embarking on a journey of discovery. But treasure is not the only thing waiting for these intrepid pigs below the ocean's surface"--Publisher's description.